Condicionalidade nas interações ecológicas: características morfológicas e variações fenológicas afetando o sistema Malpighiaceae-formiga-herbívoros - Siquieroli, Andréa Andrade Vilela (2016)
The ecological interactions are diverse and the results may vary in response to biotic and abiotic factors. Plants and ants can be associated through sugary secretions produced by extrafloral nectaries (EFNs) and the ants can also get honeydew produced by Hemiptera. Authors have demonstrated the positive effects of such interactions, however the magnitude of benefits can vary depending on morphology, physiology and behavior of ants, as well as on variations in plants reproductive events and the overlap degree between the interacting species. The Cerrado has numerous EFNs bearing plants associated with ants and honeydew producing Hemiptera and presents a seasonal phenology. Considering Malpighiaceae-antsherbivores as a model system in Cerrado, the aims were to evaluate the outcomes of ant-planthemiptera interaction considering two species of ants with different physiological and ecological adaptations to interaction (Camponotu crassus (Formicinae) and Ectatomma tuberculatum (Ectatomminae). Analyze the effects of phenological changes in ants and endophytic endophytic herbivores (Curculionids) overlap and the consequences for Banisteriospsis laevifolia and to verify the flowering strategy (synchronized or sequential) in the community composed by B. laevifolia, Banisteriospsis malifolia, Banisteriospsis campestris and Peixotoa tomentosa and the effects of different degrees of overlapping to herbivory and fruit production. The results confirmed the hypothesis of intraspecific competition of mealybugs by ant’s protection, as well as the effects of the biology of ant species in the results of interactions. The phenological changes were also proven, associated with changes in climatic factors of temperature and precipitation. The phenological variations of B. laevifolia promoted asynchrony with Curculionids and greater overlap with a sympatric species, P. tomentosa. These changes affected the ant-plant-herbivore and plant-plant interactions and confirmed the hypothesis that changes in phenology are able to affect the outcomes of key interactions and consequently the reproductive success of plants. Regarding the flowering patterns in communities, there was a differential effect on herbivory and fruit production for the four species studied. Such effects were species-specific and dependent on the closed association of these species with their pollinators and associated herbivores. The mathematical model was reliable and able to estimate the species-specific responses in situations of continuous phenological changes. Understanding how plants and animals interact is a key to understand important features of evolutionary processes. The integration of field investigations, ecological theories and mathematical models allows us to interpret the cross of important ecological interactions, describe the evolution of life history of organisms and the effects for the establishment and maintenance of the species over time. Thus, the present work contributed to a growing area of research about the inherent diversity of interactions associated with current environmental variations, making it a relevant study for a greater understanding of the ecology of the interactions and the conservation of natural communities.